The role of place in energy transitions: Siting gas-fired power stations and the reproduction of high-carbon energy systems. Issue 112 (June 2020) - Cowell, Richard
Abstract: Analysts of the spatial dynamics of energy transition have given insufficient attention to the obduracy of fossil fuel-based energy systems, and understanding such persistence requires greater analytical attention to the role of place. This paper responds to these concerns through a distinctive longitudinal, whole sector analysis of the siting decisions of 111 gas-fired power station projects in England and Wales, from 1988 to 2019. Evidence shows that over 67, 000 MW of new capacity has been consented, with few insurmountable siting problems, with place providing an important explanatory element. The fact that many projects were able to re-inhabit sites of former coal- and oil-fired power stations enabled developers successfully to mobilise arguments that gas power was a net environmental improvement, while obviating or deflecting objections based on place and landscape. The combination of site choice and consenting rules also helped gas-fired power stations nullify challenges based on the systemic risks of burning gas, and negotiate climate change policy constraints. Researchers need to theorise how 'systems of places' shape the reproduction of dominant socio-technical systems for energy, by mediating the extent and efficacy of public engagement in decision-making and problematising political challenges to the social order.